Peran Organisasi Kemahasiswaan Dalam Mengembangkan Potensi Mahasiswa Fakultas Ilmu Sosial Dan Ilmu Politik UHN Medan - Tarigan, Evan Pascal; Tobing, Artha Lumban; Sinaga, Kepler (Research and Community Service UNIVERSITAS KALBIS, 2025)
Student organizations have an important role in developing student potential, based on research conducted on students of the faculty of social and political sciences at HKBP Nommensen University, Medan, student organizations have an important role in developing student potential, such as managing time on a priority scale, developing broad insight into the environment and as a place to develop students' talents and interests. However, there are still obstacles experienced by student organizations in developing student potential, such as a lack of student enthusiasm in carrying out organizational activity programs and a lack of adequate facilities and funding which are inhibiting factors experienced by student organizations in developing student potential in the faculty of social and political sciences at HKBP Nommesen Medan University. However, student organizations continue to make efforts to carry out the programs they run and support from the faculty continues to ensure that student organizations can run optimally.